Monitoring the Emergence of SARS-CoV-2 VOCs in Wastewater and Clinical Samples—A One-Year Study in Santiago de Compostela (Spain) - Marta Lois; David Polo; María Luisa Pérez del Molino; Amparo Coira; Antonio Aguilera; Jesús L. Romalde (Viruses)
Wastewater surveillance has become a valuable tool to monitor the emergence of SARS-CoV-2 variants of concern (VOCs) at the community level. In this study, we aimed to evaluate the presence of Alpha (B.1.1.7), Beta (B.1.351), Delta (B.1617.2), and Omicron (B.1.1.529) VOCs in samples from the inlet of a wastewater treatment plant (WWTP) as well as from two different sewer interceptors (SI-1 and SI-2) from the urban sewage system in Santiago de Compostela (Galicia, NW of Spain) throughout 2021 and January 2022. For this purpose, detection and quantification of the four VOCs was performed using four duplex SARS-CoV-2 allelic discrimination RT-qPCR assays, targeting the S-gene. An N1 RT-qPCR gene assay was used as a reference for the presence of SARS-CoV-2 RNA in wastewater samples. All VOCs were detected in wastewater samples. Alpha, Beta, Delta, and Omicron VOCs were detected in 45.7%, 7.5%, 66.7%, and 72.7% of all samples, respectively. Alpha VOC was dominant during the first part of the study, whereas Delta and Omicron detection peaks were observed in May–June and December 2021, respectively. Some differences were observed among the results obtained for the two city sectors studied, which could be explained by the differences in the characteristics of the population between them. Wastewater-based epidemiology allowed us to track the early circulation and emergence of SARS-CoV-2 variants at a local level, and our results are temporally concordant with clinical data and epidemiological findings reported by the health authorities.